Strategi Guru Pendidikan Pancasila Meningkatkan Kemampuan Berpikir Kritis dan Inovatif Siswa MAN 3 Banjarmasin - Serly Serly; Zainul Akhyar (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to describe the strategies employed by Pancasila Education teachers to enhance students’ critical and innovative thinking skills and to identify the supporting and inhibiting factors in implementing these strategies at MAN 3 Banjarmasin. The study employed a qualitative approach, with data collected through observations, interviews, and documentation. Data were analyzed using the processes of data reduction, data presentation, and conclusion drawing. The findings reveal that teachers implemented student-centered learning strategies to develop students’ critical and innovative thinking skills, particularly through Problem-Based Learning (PBL) and Project-Based Learning (PjBL). Supporting factors include teachers’ competence, adequate learning facilities, and a conducive learning environment. Inhibiting factors include students’ low self-confidence, limited instructional time, differences in students’ abilities, as well as the influence of the social environment and mobile phone use. The findings further indicate that student-centered learning contributes to the development of students’ critical and innovative thinking skills at MAN 3 Banjarmasin by encouraging them to express ideas, demonstrate creativity, and think more critically and innovatively.